Financial incentives, hospital care, and health outcomes: Evidence from fair pricing laws - Benedic N. Ippolito (American Enterprise Institute (AEI), 2016)
It is often assumed that financial incentives of healthcare providers affect the care they deliver, but this issue is surprisingly difficult to study. The recent enactment of state laws that limit how much hospitals can charge uninsured patients provide a unique opportunity. Using an event study framework and panel data from the Nationwide Inpatient Sample, we examine whether these regulations lead to reductions in the amount and quality of care given to uninsured patients. We find that the introduction of a fair pricing law leads to a seven to nine percent reduction in the average length of hospital stay for uninsured patients, with no corresponding change for insured patients. These care reductions are not accompanied by worsening quality of inpatient care. Overall, our results provide strong evidence that hospitals actively alter their behavior in response to financial incentives, and are consistent with the laws promoting a shift towards more efficient care delivery. The findings also add to the growing evidence that hospitals can, and do, treat patients differently based upon insurance status.
Keywords: A; 330; health insurance